Arbutus unedo: Innovative Source of Antioxidant, Anti-Inflammatory and Anti-Tyrosinase Phenolics for Novel Cosmeceuticals - Emna Habachi; Iness Bettaieb Rebey; Sarra Dakhlaoui; Majdi Hammami; Selmi Sawsen; Kamel Msaada; Othmane Merah; Soumaya Bourgou (Cosmetics, 2022)
Phenolic compounds are valuable cosmetic ingredients. They display skin protective potential and play an important role in preserving cosmetic formulations due to their ability to neutralize free radicals. Considering this fact, the current study aims to obtain a phenolic-enriched fraction from Arbutus unedo for topical application in cosmeceutical products. The chemical composition and the antioxidant, anti-inflammatory, and anti-tyrosinase activities of different extracts from the plant were investigated and compared. Samples were obtained by maceration, reflux, and ultrasound using water and ethanol. The findings indicated that the extraction methods impacted the phytochemical composition of the extracts. The high-performance liquid chromatography with diode-array detection (HPLC–DAD) analysis showed a wide range of phenolic compounds, comprising phenolic acids and flavonoids. Among the extracts, the water reflux had significant levels of both total polyphenols, flavonoids, and tannins and possessed the most important content on hyperoside. It displayed the most significant antioxidant activities with high antiradical and reducing power, as well as strong total antioxidant activity. It possesses a promising whitening effect with high anti-tyrosinase activities. Furthermore, it shows no cytotoxicity and moderate anti-inflammatory activity. Finally, due to its high yield efficiency and activities, water reflux was selected to formulate a cosmeceutical oil-in-water nanoemulsion that displayed optimal pH and stability.